Оцінювання невизначеності вимірювань при калібруванні засобів вимірювання вологості повітря - Новосьолов, О. А. (ХНУРЕ, 2025)
The problem of estimating the uncertainty of measurements of relative air humidity measuring instruments is considered. An expression for deviations of hygrometer readings from values specified by a standard humid gas generator is written. Input quantities and their standard uncertainties are estimated. The calculation of the combined standard and expanded uncertainties when calibrating a hygrometer is performed. A measurement uncertainty budget is compiled.
Keywords: невизначеність вимірювань; вимірювання вологості повітря